Internalization of Conservation Values in Forming Green Consumption Attitude - Hadi, Syamsu; Mulyono, Kemal Budi (Fakultas Ekonomi, Universitas Negeri Semarang, 2017)
The research aims to know a friendly environmental governance system. One sector of economic governance can certainly be initiated through green consumption. The focus of the problem was the green consumption education. This research was conducted by using qualitative approach in order to reveal how the process of conservation education in the Faculty of Economics in fostering behaviors that tend to conserve the consumption behavior in this case the green consumption attitude. The collecting data of research used observation, documentation and interview. This research uncovers how the conservation education is able to shape and build the green consumption attitudes that exist among the students from planning process, implementation, and evaluation of conservation education on the aspects of green consumption. Internalization of conservation value performed by the educators (in this case the lecturers at the Faculty of Economics, Universitas Negeri Semarang) runs well enough.